Pengaruh Kepatuhan Kerja Terhadap Keselamatan Dan Kesehatan Kerja Pada Pt. Mitramas Muda Mandiri Karawang - Carma, Carma; Suheman, Enjang; Khalida, Laras Ratu (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Awareness within the company and workers of the importance of implementing occupational safety and health (K3) is very much done to prevent work accidents that can result in death or injury to workers and also material losses that are not small for the company. Occupational compliance with occupational safety and health is a key aspect in maintaining a safe and healthy work environment. This research uses research methods used using descriptive and verifiative methods, quantitative approaches with simple regression analysis methods with the help of SPSS 16 software, The population of this study was 45 employees with the sampling used, namely saturated sampling. The results of the study explained that work compliance was still below 0.05 and for the t¬-count value got a value of 6,691 where the t-table from this study was 1,676 which means that it can be concluded that work compliance has a greater value than t-table (6,691 > 1,676). Therefore, It can be concluded that the variable of Work Compliance affects Occupational Safety and health. Referring to Work Compliance and K3 at PT. Mitramas Muda Mandiri Karawang, regarding solving problems in work must be improved again. Therefore, employees must always evaluate themselves or colleagues, so that automatically the symptoms of errors can be prevented.